THE INFLUENCE OF INDEPENDENT BOARD OF COMMISSIONERS, DEFERRED TAX BURDEN, COMPANY SIZE, AND PROFITABILITY ON EARNINGS MANAGEMENT IN BASIC AND CHEMICAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE FOR THE 2021-2023 PERIOD - Kelly Chan; Laeta Maria Bernadetta Tarihoran; Siti Dini; Anggono (Mount Hope Economic Global Journal, 2024)
The government has developed the chemical industry to maintain the quality and availability of raw materials and supporting materials for other sectors. The growth of the chemical industry in Indonesia is quite rapid, as evidenced by the increasing number of issuers or chemical subsector companies listed on the Indonesia Stock Exchange each year. This study aims to determine the influence of the Independent Board of Commissioners, Deferred Tax Burden, Company Size, and Profitability on Earnings Management in Basic and Chemical Sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period. The research population consists of 28 companies in the basic and chemical subsectors listed on the Indonesia Stock Exchange during the 2021-2023 period, yielding 84 research samples. The partial results of the study indicate that the Independent Board of Commissioners has a positive and significant effect on Earnings Management, while Deferred Tax Liabilities have no significant effect on Earnings Management. Company Size has a negative but insignificant effect on Earnings Management, and Profitability has a negative and insignificant effect on Earnings Management.